Efficacy, safety, and dose response of glycopyrronium administered by metered dose inhaler using co-suspension delivery technology in subjects with intermittent or mild-to-moderate persistent asthma: A randomized controlled trial. (June 2018) - Kerwin, Edward; Wachtel, Andrew; Sher, Lawrence; Nyberg, Jack; Darken, Patrick; Siddiqui, Shahid; Duncan, Elizabeth A.; Reisner, Colin; Dorinsky, Paul
Abstract: Objectives: This randomized, double-blind, placebo-controlled, cross-over, Phase II dose-ranging study investigated the efficacy and safety of GP MDI (glycopyrronium administered by metered dose inhaler formulated using co-suspension delivery technology) compared with an open-label active comparator, salmeterol dry powder inhaler (SAL DPI), in subjects with intermittent or mild-to-moderate persistent asthma. Methods: Subjects were randomized to receive five of seven treatments (GP MDI 28.8, 14.4, 7.2, 3.6, and 1.9 μg, placebo MDI, and SAL DPI 50 μg), each for a 14-day period. The primary endpoint was peak change from baseline in forced expiratory volume in 1 s (FEV1 ) on Day 15. Secondary endpoints included additional lung function parameters and symptoms (Asthma Control Questionnaire-5). Safety was monitored throughout. Results: Of 248 subjects randomized, 211 completed the study. All doses of GP MDI resulted in significant improvements in the primary endpoint compared with placebo MDI in a dose-ordered fashion (range 85–155 mL, p < .0001), without appreciable differences between the two highest doses of GP MDI (28.8 and 14.4 μg) and SAL DPI 50 μg. Improvements in secondary lung function endpoints and symptoms were generally dose-ordered, with GP MDI 28.8 μg showing the greatest improvements. Similar results were observed when endpoints were analyzed based on subjects' background use of inhaled corticosteroids (yes/no). All GP MDI doses were well tolerated with no evidence of a dose-related effect on adverse events. Conclusions: The results of this study suggest that GP MDI could offer an important treatment option for maintenance therapy of asthma, and warrants further investigation in Phase III clinical trials.